ANALISIS BUDAYA KESELAMATAN PASIEN DI RSU PKU MUHAMMADIYAH, BANTUL - Aris Suparman Wijaya; Arlina Dewi; Della Mawros Dwita (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
Background: Patient safety culture in PKU Muhammadiyah Hospital of Bantul based on Putri (2010) in the category of enough. Though PKU Muhammadiyah Hospital of Bantul is a Class C has an obligation to implement the Patient Safety throughout the service area. Method: This study used a mixed methods research approach is a quantitative method using cross sectional and qualitative methods with case study approach with a descriptive research design. Research subjects are nurses who deal directly with patients. A total of 61 people. Measurement of patient safety culture using a questionnaire from the AHRQ (Agency for Healthcare Research and Quality) in 2004 entitled HSOPSC (Hospital Survey on Patient Safety Culture). The questionnaire consisted of 12 questions dimensions with 42 items and is equipped with the interview data and report patient safety incidents from Patient Safety Team PKU Muhammadiyah Hospital, Bantul. Results and Discussion: Patient Safety Culture at PKU Muhammadiyah Hospital of Bantul in the category of enough with a mean and median of 73.9. Still found gaps between the patient safety incident reporting patient safety teams and real in the field. As well as barriers to implementation of patient safety in PKU Muhammadiyah Hospital of Bantul is still not optimal support came from management, not optimal team performance because the work load and the persistence of blaming culture in the unit.